Effects of Enactment in Episodic Memory: A Pilot Virtual Reality Study with Young and Elderly Adults - Jebara, Najate; Orriols, Eric; Zaoui, Mohamed; Berthoz, Alain; Piolino, Pascale (Frontiers in Aging Neuroscience, 2014)
None of the previous studies on aging have tested the influence of action with respect to the degree of interaction with the environment (active or passive navigation) and the source of itinerary choice (self or externally imposed), on episodic memory encoding. The aim of this pilot study was to explore the influence of these factors on feature binding (the association between what, where and when) in episodic memory and on the subjective sense of remembering. Navigation in a virtual city was performed by 64 young and 64 older adults in one of four modes of exploration: (1) passive condition where participants were immersed as passengers of a virtual car (no interaction, no itinerary control), (2) itinerary control (the subject chose the itinerary, but did not drive the car), (3) low or (4) high navigation control (the subject just moved the car on rails or drove the car with a steering wheel and a gas pedal on a fixed itinerary, respectively). The task was to memorize as many events encountered in the virtual environment as possible along with their factual (what), spatial (where), and temporal (when) details, and then to perform immediate and delayed memory tests. An age-related decline was evidenced for immediate and delayed feature binding. Compared to passive and high navigation conditions, and regardless of age groups, feature binding was enhanced by low navigation and itinerary control conditions. The subjective sense of remembering was boosted by the itinerary control in older adults. Memory performance following high navigation was specifically linked to variability in executive functions. The present findings suggest that the decision of the itinerary is beneficial to boost episodic memory in aging, although it does not eliminate age-related deficits. Active navigation can also enhance episodic memory when it is not too demanding for subjects' cognitive resources.